2021
DOI: 10.36841/pgsdunars.v9i1.1035
|View full text |Cite
|
Sign up to set email alerts
|

Metode Blended Learning Dalam Meningkatkan Minat Belajar Mahasiswa Melalui Mata Kuliah Psikologi Pendidikan Di Masa Pandemi Covid-19

Abstract: Penelitian ini merupakan penelitian yang dilakukan dalam kondisi pandemi, yang sedang melanda dunia termasuk Indonesia saat ini, mengakibatkan interaksi tatap muka di kelas antara dosen dan mahasiswa tidak mungkin untuk dilakukan. Oleh karena itu pembelajaran digital menjadi alternatif yang penting untuk mengganti tatap muka dikellas. Namun dalam realitas sesungguhnya, banyak persoalan ketidaksiapan yang ditemukan untuk melaksanakan pembelajaran digital baik terkait dengan sarana prasarana maupun mahasiswa. Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…The blended learning method has proven to be effective for students who must learn remotely (Sefriani et al, 2021). The blended learning method is one of the solutions to meet learning needs out there since blended learning is an effective and low-risk learning method (Noervadila et al, 2021).…”
Section: B Literature Reviewmentioning
confidence: 99%
“…The blended learning method has proven to be effective for students who must learn remotely (Sefriani et al, 2021). The blended learning method is one of the solutions to meet learning needs out there since blended learning is an effective and low-risk learning method (Noervadila et al, 2021).…”
Section: B Literature Reviewmentioning
confidence: 99%
“…First, the results of this study can add to the characteristics of learning-related knowledge in the pandemic era (Larisu et al, 2020). Second, the government can be a basis for consideration to make policies that can be used in solving education problems affected by the spread of Covid-19 (Abidah et al, 2020;Sholihatun et al, 2020;Noervadila et al, 2021;Baser & Rizal, 2021).…”
Section:  Introductionmentioning
confidence: 98%
“…Using ICT will reduce the impact of the spread of the covid-19 pandemic because it can reduce face-to-face meetings as recommended by the government related to compliance with health protocols during the pandemic period (Larisu et al, 2020), (Noervadila et al, 2021). ICT encourages the delivery of flexible education caused students can learn everywhere (Abidah et al, 2020).…”
Section:  Introductionmentioning
confidence: 99%
“…In 2021, the blended-learning paradigm gained popularity (Ismaniati et al, 2016;Risnani & Husin, 2019;Noervadila et al, 2021). Blended-learning allows lecturers to conduct both face-to-face and online classes simultaneously (Benali & Ally, 2020), technically dividing classroom capacity 50% for in-person and 50% for online sessions through platforms like Zoom Meeting and Google Meet (Oktasari et al, 2018;Moya & Camacho, 2021;Noervadila et al, 2021).However, implementing this blended-learning paradigm posed several problems (Kumar & Chand, 2019). Research indicated that internet connectivity was a key issue in online learning (Grant, 2019;Cahyana et al, 2020).…”
Section: Introductionmentioning
confidence: 99%